An unusual shaped mass filling the right cardiac chambers in a woman with a vascular malformation - Podoleanu, Cristian; Balos, Sorin; Stolnicu, Simona (Polish Journal of Pathology, 2022)
We present an interesting case of a patient with uterine leiomyoma and a vascular abnormality of the internal iliac artery and peri‑uterine veins presenting a right intracardiac mass with an extremely unusual and misleading shape, requiring surgical removal and pathological examination to confirm the diagnosis.